Removal of back-reflection noise at ultrathin imaging probes by the single-core illumination and wide-field detection - Changhyeong Yoon (Nature Portfolio, 2017)
Abstract Thin waveguides such as graded-index lenses and fiber bundles are often used as imaging probes for high-resolution endomicroscopes. However, strong back-reflection from the end surfaces of the probes makes it difficult for them to resolve weak contrast objects, especially in the reflectance-mode imaging. Here we propose a method to spatially isolate illumination pathways from detection channels, and demonstrate wide-field reflectance imaging free from back-reflection noise. In the image fiber bundle, we send illumination light through individual core fibers and detect signals from target objects through the other fibers. The transmission matrix of the fiber bundle is measured and used to reconstruct a pixelation-free image. We demonstrated that the proposed imaging method improved 3.2 times on the signal to noise ratio produced by the conventional illumination-detection scheme.